Susceptibility of laboratory rodents to Trichinella papuae - Lakkhana Sadaow (2018)
Members of the genus Trichinella are small nematodes that can infect a wide range of animal hosts. However, their infectivity varies depending on the parasite and host species combination. In this study, we examined the susceptibility of 4 species of laboratory rodents, i.e., mice, rats, hamsters, and gerbils to Trichinella papuae, an emerging non-encapsulated Trichinella species. Trichinella spiralis and Trichinella pseudospiralis were also included in this study for comparison. Fifteen animals of each rodent species were infected orally with 100 muscle larvae of each Trichinella species. Intestinal worm burden was determined at day 6 and 10 post-inoculation (PI). The numbers of muscle larvae were examined at day 45 PI. The reproductive capacity index (RCI) of the 3 Trichinella species in different rodent hosts was determined. By day 6 PI, 33.2-69.6% of the inoculated larvae of the 3 Trichinella species became adult worms in the small intestines of the host animals. However, in rats, more than 96% of adult worms of all 3 Trichinella species were expelled from the gut by day 10 PI. In gerbils, only 4.8-18.1% of adult worms were expelled by day 10 PI. In accordance with the intestinal worm burden and the persistence of adults, the RCI was the highest in gerbils with values of 241.5±41.0 for T. papuae, 432.6±48 for T. pseudospiralis, and 528.6±20.6 for T. spiralis. Hamsters ranked second and mice ranked third in susceptibility in terms of the RCI, Rats yielded the lowest parasite RCI for all 3 Trichinella species. Gerbils may be an alternative laboratory animal for isolation and maintenance of Trichinella spp. © 2013, Korean Society for Parasitology and Tropical Medicine.